Desain Perangkat Aktif Data Center Berdasarkan Standar TIA-942 Tingkat 3 - Jeckson Sidabutar (J I M P - Jurnal Informatika Merdeka Pasuruan, 2022)
The development of Information and Communication Technology (ICT) provides solutions in running the company's business processes and the convergence of ICT services. It shows the increasing vital role of ICT and impacts the increasing demand for data storage and processing. One of the uses of ICT in data storage and processing is the Data Center (DC). DC contains electronic equipment facilities used for data processing (server), data storage (storage equipment), and communication (network equipment), which aims to support the business continuity of a company. The DC network supports cloud-inspired environments and extends its functionality into a public cloud provider infrastructure. The makes DC one of the ICTs used by several parties (e-Government, e-Education, e-Commerce, etc.) and increases DC growth worldwide and energy consumption efficiency. This study designs DC active devices based on the TIA-942 Tier 3 standard and provides recommendations to stakeholders in determining the brand/vendor of active devices based on the Gartner MQ benchmark. The design of DC active devices can function as an operation center and service provider, thereby improving business processes and services to the community in all SKPDs in XYZ Province.